The Influence of the Laser Power on the Manufacturing Quality Specific to Automotive Parts - Dumitrascu Dorin-Ion; Rusu Alexandru-Nicolae; Dumitrascu Adela-Eliza (E3S Web of Conferences)
The aim of this paper is to analyze the influence of laser power on the micro-perforation process of automotive parts. From a statistical point of view, the Anderson-Darling normality test was applied to validate the data distribution. With a 95% confidence interval, the goodness-of-fit is justified by the Anderson-Darling statistics (A-Squared = 0.14, P-Value = 0.963), indicating that the data are homogeneous. The summary report revealed that the mean laser power is 0.342 W, with confidence intervals ranging from 0.271 W to 0.413 W, and a standard deviation of 0.116 W, with confidence intervals between 0.083 W and 0.193 W. Furthermore, the analysis showed low variance, a skewness of 0.171 W, and a kurtosis of - 0.566 W. In conclusion, the study highlights the importance of precise control over laser power in the micro-perforation process, providing valuable insights for industrial applications aimed at improving the quality of automotive parts.